Ethical law suits from the Regional Council of Dentistry of Pará state from 2007 to 2010 (Saúde Ética & Justiça, 2013)
With dental health professionals becoming ever more subject to ethical law suits, there is, without question, a need to safeguard against possible accusations of patients and professional colleagues. In this paper, the authors analyze quantitative aspects related to ethical processes in the Regional Council of Dentistry from Pará, Brazil State (CRO-PA) from January 2007 to December 2010. From The documents provided by CRO-PA (n=67) it was possible to observe that malpractice and imprudence were the main issues of complaint (related to acquired results) being 40.3 % of the cases, followed by irregularity (26.9 %), misuse of marketing (19.4 %) and embarrassment (7.5 %). These data showed that the general population understands bad treatment as a result of a lack of professional training and that there is a need for a better preparation when marketing and propaganda are in state. The acquired data suggest that the general population understands bad results as a lack of appropriate technical preparation of the dentists and, there is, among these professionals, a need for more knowledge related to ethics in marketing and advertising.